Case of Schizophrenia and Obsessive Compulsive Disorder - Sankaran, Rajan (Homœopathic Links, 2013)
In Psychiatric cases one can use the Sensation method with good effectiveness. By going with the patient through his delusion into his sensation, one can identify the kingdom and subkingdom to which it belongs. Used in conjunction with the symptomatic approach, it makes the selection of the remedy more definite.
Keywords: Schizophrenia; Obsessive compulsive disorder; Carbons; Carbo vegetabilis